MARIKANA, A PAST NEVER TRULY ESCAPED: A CRITIQUE ON THE COMMODIFICATION OF THE LEGAL SYSTEM AND THE LAW AS AN INSTRUMENT OF JUSTICE IN POST-APARTHEID SOUTH AFRICA (The Pretoria Student Law Review, 2021)
This article demonstrates that the Marikana tragedy was not a departure from the norm, but a continuation of state and corporate behaviour that has oppressed black South Africans for hundreds of years. This will be done through an analysis of the historically discriminatory socio-economic patterns of South African society, and how they subjugate the poor by limiting their access to legal and physical protection. These trends portray a history of commodification of the legal system. I discuss a notable documentary on the massacre, Miners Shot Down, and examine its depiction of the causes and effects of the events. The film provides no mention of the historical context of the killings, nor does it comment on many of the factors contributing to the massacre. Despite this, it succeeded in bringing the events to the attention of the broader public. I analyse the notions of justice, the rule of law and their application in South Africa as well as norms in the nation’s legal culture. Additionally, I examine the Farlam Commission, and how its procedures and conclusions hindered the course of justice in the context of our democracy. Ultimately, I demonstrate how the Marikana massacre was not a change in dynamic, but a reminder of a past we have never truly escaped.
Keywords: Marikana tragedy; oppressed black South Africans; historically discriminatory socio-economic patterns; justice; rule of law; Farlam Commission